Social Media Recruitment: Communication Characteristics and Sought Gratifications - Carpentier, Marieke; Van Hoye, Greet; Weng, Qingxiong (Frontiers in Psychology, 2019)
This study examines how social media pages can be used to influence potential applicants’ attraction. Based on the uses and gratifications theory, this study examines whether organizations can manipulate the communication characteristics informativeness and social presence on their social media page to positively affect organizational attractiveness. Moreover, we examine whether job applicants’ sought gratifications on social media influence these effects. A 2x2 between-subjects experimental design is used. The findings show that organizations can manipulate informativeness and social presence on their social media. The effect of manipulated informativeness on organizational attractiveness depends on the level of manipulated social presence. When social presence was high, informativeness positively affected organizational attractiveness. This positive effect was found regardless of participants’ sought utilitarian gratification. Social presence had no significant main effect on organizational attractiveness. There was some evidence that the effect of social presence differed for different levels of social gratification.